Answer:
2(x-3)² - 11 where a = 2, b = -3, c = -11
Explanation:
Taking the first 2 terms,
2x² - 12x ==> 2(x² -6x) [1]
x² -6x can be rewritten as (x -3)² - 9 [2]
since (x-3)² = x² -6x + 9
Substituting for x² -6x in [1] we get
2(x² -6x) = 2((x -3)² - 9 ) = 2(x-3)² -18
Therefore substituting for 2x² - 12x in the original equation we get
2x² - 12x + 7 = 2(x-3)² -18 + 7 ==> 2(x-3)² -11
this is in the form (a(x+b) + c where a = 2, b = -3 and c= -11
Cross-check
2(x-3)² - 11 ==> 2 (x² -6x +9) -11 ==> 2x² -12x +18 - 11 ==> 2x² -12x + 7